Pedagogues' Competencies for Engouraging and Developing Professional Development of Teachers - Drago J. Branković; Мargareta G. Skopljak; Draženko. L. Jorgić (University of Belgrade, Teacher Education Faculty, 2020)
Competencies for encouraging and developing teachers' professional development are only one of the elements of developmental and professional competencies of pedagogues. The results of the research conducted so far have shown that competencies are not sufficiently compatible with personal and professional needs, and that there is a lack of research on the level of competence by functions and areas of work of pedagogues. The aim of the research was to identify according to the pedagogues' self-reporting, i.e., self-assessment the differences in the levels of development of their competencies and in the levels of their involvement in encouraging and developing the professional development of teachers relative to certain socio-demographic characteristics of the pedagogues. The research was conducted by applying a survey as the research method and the scaling technique on a sample of 78 pedagogues. The research results (basic and three special hypotheses) showed that school pedagogues have a high level of competence and involvement in encouraging and developing the professional development of teachers, but that the differences in the levels relative to certain socio-demographic characteristics are not statistically significant. The key implications of the research relate to the need to critically consider the curriculum of the pedagogy studies, the quality and content of the professional development programs as a methodological justification for involving teachers in the research of the pedagogues' competencies.